Improving Student Learning Outcomes in Determining the Area and Perimeter of Flat Shapes Through the Use of Drill Method - Arni, Yusni; Andira, Ari Okta; Nabilla, Ganta; Mursiani, Mursiani (Continuous Education: Journal of Science and Research, 2024)
Interaction between students, teachers, and learning materials in a classroom setting constitutes the process of learning. The system that makes up the learning environment is made up of teachers, students, learning materials, strategies, and tools. Therefore, the following is the goal of increasing learning: Increasing student learning outcomes in the area of area and perimeter of flat buildings through the implementation of the drill method in the mathematics learning process. There were twenty pupils in class IV at SD Cita Hati Surabaya, nine of them were male and eleven of whom were female, working on the repairs. The examination and discussion of the aforementioned challenges yielded results that demonstrate how teachers implement the learning improvement program in order to enhance students' learning outcomes in the topic of mathematics. Using the drill approach can improve students' learning objectives of "Area and Perimeter of Flat Shapes" in mathematics class. Student learning outcomes after using the drill method show an increase in significance towards their learning objectives.